The impact of COVID-19: Psychosocial risks on non-university teachers - Gómez Domínguez, Valentina; Gómez Domínguez, M. Teresa; Sánchez Pujalte, Laura; Navarro Mateu, Diego (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Objective: To analyse the psychosocial risks suffered by teachers during the pandemic. Method: Descriptive analysis, correlations and comparison of means. Sample: 265 non-university teachers. Instruments: Validated questionnaire extracted from UNIPSICO Battery, Burnout Assessment- BAT and Job Insecurity Scale and ad-hoc questionnaire to measure resources, information, measures and impact. Results: Inequity followed by overload are the biggest risks. Perceived lack of organisational justice, role and interpersonal conflict, increased workload. High social support. Insufficient resources, information and measures and moderate-high impact on their professional performance. Non-significant values for burnout and health.